Comparison of 316L stainless steel parts produced by MEX and LPBF additive and conventional manufacturing for biomedical sensing applications (Transactions on Additive Manufacturing Meets Medicine, 2024)
This study presents a comprehensive evaluation of force sensors manufactured through conventional CNC machining, laser powder bed fusion (LPBF), and material extrusion (MEX) 3D printing methods. The study utilized a combination of finite element method (FEM) simulations, functional testing, durability assessments, and ultimate strength testing in order to assess the viability of additive manufacturing for sensing technology applications. The FEM simulations provided a preliminary framework for predictive analysis, closely aligning with experimental outcomes for LPBF and conventionally manufactured sensors. Nevertheless, discrepancies were observed in the performance of MEX-printed sensors during ultimate strength testing, necessitating the implementation of more comprehensive modeling approaches that take into account the distinctive material characteristics and failure mechanisms. Functional testing confirmed the operational capability of all sensors, thereby demonstrating their suitability for the intended application. Moreover, all sensors exhibited resilience during 50,000 cycles of cyclic testing, indicating reliability, durability, and satisfactory fatigue life performance. Notably, sensors produced via LPBF exhibited a significant increase in strength, nearly three times that of conventionally manufactured sensors. These findings suggest the potential for innovative sensor design and the expansion of their use into higher-loaded applications. Overall, while both LPBF and conventional methods demonstrated reliability and closely matched simulation predictions, further research is necessary to refine modeling approaches for MEX-printed sensors and fully unlock their potential in sensing technology applications. These findings indicate that additive manufacturing of metals may be a viable alternative for the fabrication of biomedical sensors.
Keywords: Additive Manufacturig; metallic additive manufacturing; Compression Testing; FEM; laser powder bed fusion; MEX; Mechanical Properties; mechanical testing; sensing application